The Students' Written Response Improvements In Literature Circles Program (A case study of one public high school in Demak) - Saadati, Nur Aini (2011)
This thesis reports on the effectiveness of Literature Circles in improving the students' written responses, the types of students' written responses and their perspectives about the program. The study was conducted at one private high school in Demak. It involved a class of 30 students, grade XI. The program was conducted in five weeks, 28 April - 28 May 2010. Literature Circles had been nurtured and covered up 4 cycles of Literature Circles. This study employed a program evaluation, and embraced the characteristics of case study. The data were obtained from several sources. It included the classroom observations, interview and document analysis. The collections of the students' texts were analyzed using the stances continuum proposed by Cox and Manny (1992), and the responses categories by Squire (1964) & Thomson (1987). The findings revealed that the program was to some extent successful in improving the students' written responses in that they were better at expressing ideas. The results also showed that the students' written responses revealed at all points of the stances continuum in varied distribution. However, the written responses were mostly at the primarily efferent and primarily aesthetic points. As well as generally, the students enjoyed doing Literature Circles in their English class. With reference to the findings, it is recommended that Literature Circles be incorporated in the teaching of English for other language skills improvements (e.g. speaking and listening). It is also recommended that Literature Circles may be applied in the class other than English.